Pengaruh Kompensasi dan Budaya Organisasi terhadap Kinerja Karyawan di MEC (Mastin Education Center) - Umi Salamah; Rian Fahrijin; Bangun Putra Prasetya (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study investigates how compensation and organizational culture impact employee performance at Mastin Education Center (MEC). Employee performance is critical to achieving organizational goals, especially in the era of globalization and increasing competition. Therefore, this study is based on this understanding. This study used a quantitative method with a survey design, and used a saturated sampling technique for every ten MEC workers. Data were collected through questionnaires and analyzed using multiple linear regression using IBM SPSS Statistic 26. The t-test results showed that compensation (significance value 0.235) did not significantly affect employee performance. In contrast, organizational culture (significance value 0.001) had a positive impact. The F test results show that compensation and organizational culture simultaneously affect employee performance (significance value 0.005). An Adjusted R Square value of 0.800 indicates that these two factors can explain 80 percent of the variation in employee performance. Other factors not included in this study influence the remaining variation. These findings suggest that improving organizational culture and updating the compensation system are critical to improving employee performance.